Gap Junctions Are Involved in the Rescue of CFTR-Dependent Chloride Efflux by Amniotic Mesenchymal Stem Cells in Coculture with Cystic Fibrosis CFBE41o- Cells - Annalucia Carbone; Roberto Zefferino; Elisa Beccia; Valeria Casavola; Stefano Castellani; Sante Di Gioia; Valentina Giannone; Manuela Seia; Antonella Angiolillo; Carla Colombo; Maria Favia; Massimo Conese (Stem Cells International)
We previously found that human amniotic mesenchymal stem cells (hAMSCs) in coculture with CF immortalised airway epithelial cells (CFBE41o- line, CFBE) on Transwell® filters acquired an epithelial phenotype and led to the expression of a mature and functional CFTR protein. In order to explore the role of gap junction- (GJ-) mediated intercellular communication (GJIC) in this rescue, cocultures (hAMSC : CFBE, 1 : 5 ratio) were studied for the formation of GJIC, before and after silencing connexin 43 (Cx43), a major component of GJs. Functional GJs in cocultures were inhibited when the expression of the Cx43 protein was downregulated. Transfection of cocultures with siRNA against Cx43 resulted in the absence of specific CFTR signal on the apical membrane and reduction in the mature form of CFTR (band C), and in parallel, the CFTR-dependent chloride channel activity was significantly decreased. Cx43 downregulation determined also a decrease in transepithelial resistance and an increase in paracellular permeability as compared with control cocultures, implying that GJIC may regulate CFTR expression and function that in turn modulate airway epithelium tightness. These results indicate that GJIC is involved in the correction of CFTR chloride channel activity upon the acquisition of an epithelial phenotype by hAMSCs in coculture with CF cells.